Performance of solar absorber shieldings on energy reception. - Ahmad, Mohammad Nur (1986)
Investigations into the use of 3 types of absorber tube shieldings with respect to heat losses were carried out. In this study a cylindrical parabolic solar concentrator was used to direct beam radiation on to the absorber-shielding configurations and tests were conducted in a wind-tunnel under varying wind speeds and absorber temperatures. Several wind speeds and temperature ranges were used to reflect local weather conditions. The study recorded reduction in heat losses due to shieldings. Also, percentage reduction in energy interception was found to be least with one glass shield arrangement. The equations of Duffie and Beckman and Kuehn and Goldstein in respect of heat loss calculations were used. Their predictions agreed well with, experimental results in most cases investigated.